Availability and Affordability of Oncology Drugs in 2012-2021 in China and the United States - Huang, Huiyao; Zhu, Qi; Ga, Man; Wu, Dawei; Meng, Xinyu; Wang, Shuhang; Fang, Hong; Tang, Yu; Li, Ning (Frontiers in Oncology, 2022)
Objective To systematically summarize the landscape and characteristics of all approved new anticancer drugs for the last 10 years in China and the United States (US) to further inform the trend, current state, and existing gap in the availability and affordability of cancer medicine between the two countries. Methods Mainly based on the Pharmcube database, a list and detailed information of anticancer drugs approved in China and the United States were acquired. The annual number, time lag, and basic characteristics, including drug type, mechanism, enterprise type, indication population, drug target, and cancer type of approved drugs were compared. Results Eighty-seven and 118 new anticancer drugs were approved in China and the US, respectively, showing a stable trend in the US, while a significant increase was observed after 2016 in China. Of the 42 cancer medicines launched in both countries, the US took precedence, and the median time lag markedly decreased, from 6.53 years in 2012 to 0.88 years in 2020. A total of 14.4% of drugs were applicable to children in the US, while only 2.3% were applicable in China, and there was no difference in drug type and enterprise. Thirty-one and 43 targets were explored, with respect to 27 and 36 cancer types in China and the US, respectively, during the period. In addition, the expenditure of drugs on PD-1 and PD-L1 in China was generally lower than that in America. Conclusion The availability of new anticancer drugs has increased dramatically in the past decade, particularly in China. Compared with the US, the launch of new anticancer drugs in China lags behind, but the time lag has been shortened significantly, and better affordability is observed in immune drugs. More attention should be given to differentiated innovation, and unmet medical needs in special populations like childhood tumors, which are important directions of new drug R&D in China.